A Dual Band Transmittive-type Linear to Circular Polarization Converter using Single Layer Metasurface - Kumar R.; Mishra V.K.; Mukherjee B.; Kumar V.; Kumar A.P.; Dhar J.; Bhattacharyya S. (My University, 2025)
This manuscript presents a novel metasurface (MS) based structure which can convert a transmittive-type linearly polarized incident electromagnetic (EM) wave into circularly polarized one in two distinct frequency bands incorporating a single layer of dielectric. The unit cell of the MS comprises six diagonally arranged metallic small square patches enclosed by a metallic square ring at the edge. The proposed structure has been designed on a λ/32 thick dielectric substrate along with the periodicity of λ/5 where λ is free space wavelength with respect to the center frequency of the lower conversion band. The transmitted EM wave is circularly polarized (CP) in nature in C and Ku bands as the axial ratio is below 3 dB at 5.34 GHz to 6.8 GHz and 13.3 GHz to 16.01 GHz, being centered at 6 GHz and 14.5 GHz respectively. The chirality and surface current have been studied to confirm that the transmitted waves are respectively left-handed CP and right-handed CP in C and Ku bands. The proposed structure can find potential applications towards space and satellite communications. © 2024 IEEE.